Dynamic Modeling of Hydrogen Production from Photo-Fermentation in Microbial Electrolysis Cell using Sago Waste - Atan, Mohd Farid; Hafizah, Abdul Halim Yun; Josephine, Chang Hui Lai; Md Rezaur, Rahman; Mohammad Omar, Abdullah; Noraziah, Abdul Wahab (2020)
Hydrogen has a great potential as an alternative energy and produces zero emissions, but most of hydrogen is produced from non-renewable fossil fuels via reforming. Thus, biomass is a promising replacement to fossil fuels where hydrogen can be sourced from. In this project, sago waste is chosen as raw material in a microbial electrolysis cell (MEC) to produce hydrogen fuel. A mathematical model with the integration of MEC with photo-fermentation has been developed and modified by using sago effluent as a substrate in a batch process. The main parameter such as concentration of microbial community has been observed in this project as it gives a huge influence on the gas product of MEC. In conclusion, the develop model was to observe the behavior of the microbial electrolysis cell where a maximum of 3.8 L/day (t = 4 days) of hydrogen production and 0.38A of MEC current were obtained.